2019
DOI: 10.31234/osf.io/5gjac
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human handedness: A meta-analysis

Abstract: Across time and place, right hand preference has been the norm, but what is the precise prevalence of left- and right-handedness? Frequency of left-handedness has shaped and underpinned different fields of research, from cognitive neuroscience to human evolution, but reliable distributional estimates are still lacking. While hundreds of empirical studies have assessed handedness, a large-scale, comprehensive review of the prevalence of handedness and the factors which moderate it, is currently missing. Here, w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
72
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(82 citation statements)
references
References 38 publications
8
72
1
1
Order By: Relevance
“…Hand preference for writing can be easily collected as a tick-box questionnaire leading to large datasets. A recent meta-analysis estimated that the prevalence of left-hand preference in the general population is 10.6% based on data from over 2 million of people [11]. The study also confirmed the effect of some factors influencing hand preference including age, sex, and ethnicity reported in previous research.…”
Section: Handedness In Chinese Samplessupporting
confidence: 79%
See 2 more Smart Citations
“…Hand preference for writing can be easily collected as a tick-box questionnaire leading to large datasets. A recent meta-analysis estimated that the prevalence of left-hand preference in the general population is 10.6% based on data from over 2 million of people [11]. The study also confirmed the effect of some factors influencing hand preference including age, sex, and ethnicity reported in previous research.…”
Section: Handedness In Chinese Samplessupporting
confidence: 79%
“…Our results show that, using a binary classification of writing hand as the criterion, around 8% of school-aged children are left-handers. This estimate is lower than the most recently published value of 10.6% for the general left-handedness prevalence[11],…”
contrasting
confidence: 73%
See 1 more Smart Citation
“…Worldwide, the vast majority of people (roughly 90%) prefer using the right hand for most tasks in contrast to a minority of about 10% who prefer the left hand (1,2). The rightward prevalence of handedness is a feature specific to humans.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it is well established that environmental factors might force the use of the right hand for writing in people who might prefer using the left hand (10). This phenomenon was mainly true for past generations, and still applies in some cultures (1,11). Typically, handedness questionnaires are characterised by a J-shaped distribution, indicating that the majority of people present an overall right-or left-hand preference with a few individuals in between.…”
Section: Introductionmentioning
confidence: 99%